2016
DOI: 10.1111/bjh.14302
|View full text |Cite
|
Sign up to set email alerts
|

Ibrutinib‐associated rash: a single‐centre experience of clinicopathological features and management

Abstract: . (2015) Association of an alpha-globin gene cluster duplication and heterozygous betathalassemia in a patient with a severe thalassemia syndrome. Hemoglobin, 39, 102-106.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(87 citation statements)
references
References 6 publications
4
83
0
Order By: Relevance
“…In Phase III clinical trials of ibrutinib in CLL, any grade rash was reported in 8% of patients in the RESONATE study and grade ≥3 rash was reported in 3% of patients in RESONATE‐2 (Byrd et al , ; Burger et al , ). While most of the current understanding of ibrutinib‐associated rash comes from individual case reports (Mannis et al , ; Jensen et al , ), reports of larger patient groups being assessed for clinicopathological features, treatment methods and outcomes are starting to emerge (Iberri et al , ). It is the authors' experience that most patients who develop rash have prior history of hypersensitivity to other agents.…”
Section: Resultsmentioning
confidence: 99%
“…In Phase III clinical trials of ibrutinib in CLL, any grade rash was reported in 8% of patients in the RESONATE study and grade ≥3 rash was reported in 3% of patients in RESONATE‐2 (Byrd et al , ; Burger et al , ). While most of the current understanding of ibrutinib‐associated rash comes from individual case reports (Mannis et al , ; Jensen et al , ), reports of larger patient groups being assessed for clinicopathological features, treatment methods and outcomes are starting to emerge (Iberri et al , ). It is the authors' experience that most patients who develop rash have prior history of hypersensitivity to other agents.…”
Section: Resultsmentioning
confidence: 99%
“…Rash is a common ibrutinib side effect in 2-27% of patients 3,5,24,28 , but is often self-limited or easily managed with topical steroids 74,75 . A case series of 14 patients has been published from Stanford, in which two categories of rash were identified 74 .…”
Section: Dermatologic Changesmentioning
confidence: 99%
“…A case series of 14 patients has been published from Stanford, in which two categories of rash were identified 74 . The first was a non-palpable asymptomatic petechial rash, perhaps related to ibrutinib-induced platelet dysfunction, while the second was a palpable pruritic rash which on biopsy showed an inflammatory infiltrate.…”
Section: Dermatologic Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the rate of grade ≥3 adverse events remains low and treatment discontinuation due to toxicity (Byrd et al , , ) is uncommon and mostly related to infections (Byrd et al , , ; Burger et al , ; Puła et al , ; Tran & O'Brien, ). Dermatological toxicities have also been reported in 2–27% of treated patients (Ransohoff & Kwong, ; Iberri et al , ), mainly mild‐to‐moderate rash, neutrophilic panniculitis, progressive hair and nail changes, skin infections, bruising, petechiae and purpuric eruption (Fabbro et al , ; Bitar et al , ; Ransohoff & Kwong, ; Iberri et al , ). In contrast, oral toxicity with ibrutinib has rarely been described.…”
Section: Clinical Features Of Chronic Lymphocytic Leukaemia Patients mentioning
confidence: 99%